Research on patients' willingness to conduct online health consultation from the perspective of web trust model - Xu, Yongxun; Yang, Zishuo; Jiang, Hongyan; Sun, Peizhen (Frontiers in Public Health, 2022)
Background and Aims: The online health platform becomes an important choice for users to receive health services. While bringing convenience to users, it also provides lots of overloaded information for users and leads them to have trouble in making online medical choice decisions. In order to understand what types of information on the online health platform play key roles in the user’s decision choice, this research explores the effects of cognition-based information, affect-based information and institution-based information on patients’ willingness to conduct online health consultation from the perspective of Web Trust Model. Methods: Responses of 412 valid questionnaires were collected via online surveys. Results: The results showed that: (1) cognition-based information, affect-based information and institution-based information positively predict patients’ willingness to conduct online health consultation; (2) online trust significantly mediates the relationship between online health platform information and willingness to conduct online health consultation; (3) health consciousness significantly moderates the mediating effect of online trust in the effect of online health platform information on patients’ willingness to conduct online health consultation. Conclusions: The findings make theoretical contributions by extending the Web Trust Model to the research field of online health service and offers practical implications for how to effectively provide information on the online health platform.